Stable Perovskite Quantum Dots Light‐Emitting Diodes with Efficiency Exceeding 24% - Xuanyu Zhang; Qiangqiang Wang; Zhiwei Yao; Ming Deng; Jing Wang; Lei Qian; Yong Ren; Yuying Yan; Chaoyu Xiang (Advanced Science, 2023)
Abstract Perovskite nanocrystals for light‐emitting diodes are often synthesized by uncontrollable metathesis reactions, suffering from low product yield, nonuniform growth, and poor stability. Herein, by controlling the nucleation kinetics with high dissociation constant (Ka or Kb) acids or bases, homogenous one‐route nucleation of perovskite nanocrystals is achieved as the cluster intermediates are eliminated. The stable, shape uniform, and narrow size distribution green nanocrystals are synthesized. The perovskite nanocrystal film exhibites excellent stability in 80% humidity air with only a 10% photoluminescence intensity drop after 16 h. Efficient and stable electroluminescence is demonstrated with an FWHM of 16 nm at 517 nm. The green devices shows a peak EQE of 24.13% with a lifetime T50 of 54 min at 10 000 cd m−2.